2007
DOI: 10.1084/jem.20062299
|View full text |Cite
|
Sign up to set email alerts
|

Conditional inactivation of Fbxw7 impairs cell-cycle exit during T cell differentiation and results in lymphomatogenesis

Abstract: Cell proliferation is strictly controlled during differentiation. In T cell development, the cell cycle is normally arrested at the CD4+CD8+ stage, but the mechanism underlying such differentiation-specific exit from the cell cycle has been unclear. Fbxw7 (also known as Fbw7, Sel-10, hCdc4, or hAgo), an F-box protein subunit of an SCF-type ubiquitin ligase complex, induces the degradation of positive regulators of the cell cycle, such as c-Myc, c-Jun, cyclin E, and Notch. FBXW7 is often mutated in a subset of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
188
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 173 publications
(202 citation statements)
references
References 49 publications
12
188
2
Order By: Relevance
“…The deregulation of cyclin E expression caused by mutation of FBXW7 thus likely contributes directly to the development of at least a subset of human tumors. However, the observations that the abundance of cyclin E was not increased either in the thymic lymphomas that develop in mice with conditional ablation of Fbxw7 (Fbxw7 D/D mice) (Onoyama et al, 2007) or in the radiation-induced lymphomas that are frequently observed in Fbxw7 þ /À mice (Mao et al, 2004) suggest that Fbxw7 contributes to cyclin E proteolysis in a contextdependent manner.…”
Section: Introductionmentioning
confidence: 80%
See 2 more Smart Citations
“…The deregulation of cyclin E expression caused by mutation of FBXW7 thus likely contributes directly to the development of at least a subset of human tumors. However, the observations that the abundance of cyclin E was not increased either in the thymic lymphomas that develop in mice with conditional ablation of Fbxw7 (Fbxw7 D/D mice) (Onoyama et al, 2007) or in the radiation-induced lymphomas that are frequently observed in Fbxw7 þ /À mice (Mao et al, 2004) suggest that Fbxw7 contributes to cyclin E proteolysis in a contextdependent manner.…”
Section: Introductionmentioning
confidence: 80%
“…We have previously shown that abnormal accumulation of NICD1 and c-Myc and the associated overproliferation of thymocytes resulted in thymic lymphoma in mice with conditional inactivation of Fbxw7 in the T-cell lineage (Onoyama et al, 2007). Additional ablation of the c-Myc gene in Fbxw7 D/D T cells reversed the overproliferation phenotype.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As a component of the UPS, Fbw7 ubiquitin ligase plays a vital role in cell fate decisions (35,42). It was recently shown that Fbw7 controlled the fate of hematopoietic stem cells (43) and affected the proliferation and lymphomagenesis of mouse T cells (44), both through the regulation of c-Myc expression. In addition, as a tumor suppressor, Fbw7 is inactivated in numerous human malignancies.…”
Section: Discussionmentioning
confidence: 99%
“…However, how Fbw7 suppresses tumor formation is currently not well understood. Although negative regulation of c-Myc and NOTCH-1 by Fbw7 has been implicated in tumorigenesis, their contributions to the tumor suppressor function of Fbw7 still require substantial characterization [16,[18][19][20]. On the other hand, cyclin E has garnered much attention as a possible key mediator for the ability of Fbw7 to inhibit tumorigenesis.…”
Section: Introductionmentioning
confidence: 99%